Four-dimensional computed tomography detects dynamic three-dimensional pathologies of the wrist in patients with calcium pyrophosphate deposition disease - Ulas, Sevtap Tugce; Pochandke, Louise; Ohrndorf, Sarah; Diekhoff, Torsten; Ziegeler, Katharina (Frontiers in Medicine, 2023)
Objectives Crystal deposits in ligaments of the wrist are typical findings in patients with calcium pyrophosphate deposition (CPPD) disease. CPPD crystals trigger inflammation and ultimately result in ligament tears with scapholunate (SL) advanced collapse (SLAC). This study aimed to investigate carpal instabilities in patients with CPPD using four-dimensional computed tomography (4D-CT) of the wrist. Methods This IRB-approved prospective feasibility study investigated patients with CPPD of the hand. All patients underwent a static 3D-CT and two dynamic 4D-CT in ulnar- and radial abduction and in supination and pronation movements to analyze instabilities of the SL region and of the distal radioulnar joint (DRUJ). Two independent readers scored the images for the presence of SL ligament and triangular fibrocartilage complex (TFCC) calcifications. Furthermore, the readers assessed the dynamic images for SL and DRUJ instabilities. Descriptive analyses were performed. Inter-rater reliability was assessed using Cohen’s kappa (κ). Results Nine patients were included. SL ligament calcifications and instabilities were found in all patients. Of these, dynamic SL instability was detected in 77.8% of the patients, while 22.2% had a SLAC wrist. TFCC calcifications were found in 87.5% of the patients. Four patients had DRUJ instability (50%). No patient showed DRUJ instability without the presence of TFCC calcifications. Agreement between readers for calcifications was excellent (κ = 1) and almost perfect (κ = 0.89) for instabilities. Conclusion This study provides the first evidence of relevant dynamic carpal instability in CPPD patients using advanced imaging techniques with 4D-CT, offering unique insights into wrist biomechanics.